Demographic and Anthropometric Variables Related to Longevity: Results from a Greek Centenarians’ Study - Christina Darviri; Panagiotis Pelekasis; Michael Galanakis; Xanthi Tigani (Journal of Basic & Applied Sciences, 2015)
Centenarian research contributes to expanding our knowledge on longevity and healthy aging. In Greece, a variety of studies have been conducted in order to explore exceptional longevity. This is a retrospective study of 106 centenarians employing both quantitative and qualitative measures in order to explore centenarians own perspective on longevity. Basic socio demographic and life style variables where associated with centenarians beliefs and perceptions about their longevity. The majority of centenarians attributed their longevity to God and to living a good life overall. God and social networks were reported as their main source of strength in order to continue living. Gender differences were also evident as male centenarians reported non abusive behaviors and a sense of having a measure in daily living, as well as nutrition as their main source of longevity, while female emphasized on God and social networks. Gender differences on Body Mass Index and Smoking are also evident. Centenarians own perception of longevity could be further explored and findings could be incorporated in future research and intervention programs aiming at healthy longevity.